Analisis keunggulan bersaing UMKM ditinjau dari aspek modern marketing mix 4PS pada UMKM di kota Pematangsiantar - Julyanthry Julyanthry; Debi Eka Putri; Nana Triapnita Nainggolan; Novita Butarbutar; Acai Sudirman (Jurnal Ilmu Manajemen, 2023)
Modern Marketing Mix 4Ps focus marketing activities on four pillars: people, process, programs, and performances. With these four pillars, marketers can create campaigns that effectively reach the target audience across various promotional channels to promote products. This study aims to analyze the influence of the Modern Marketing Mix 4Ps in terms of people, processes, programs, and performances on the competitive advantage of MSMEs in Pematangsiantar City. This study's research method includes library and field research design with a quantitative approach. The research subjects taken in this study were SME actors in the culinary sector in Pematangsiantar City. Data collection techniques using observation, interviews, questionnaires, and documentation. The data analysis method used is Partial Least Square (PLS). The data analysis test tool uses the Smartpls statistical software. The study stated positive and significant results between processes, people, programs, performance, and competitive advantage. The conclusion of this study explains that in determining a good 4PS marketing strategy, business actors should need to determine the process, price, and place, promote the right product, determine the packaging and process, and add human resources who work professionally.